A comparison of traditional and quantitative analysis of acid–base imbalances in hypoalbuminemic dogs. (20th August 2014) - Torrente, Carlos; Manzanilla, Edgar G.; de Gopegui, Rafael Ruiz
Abstract Objective To compare the traditional (HH) and quantitative approaches used for the evaluation of the acid–base balance in hypoalbuminemic dogs. Design Prospective observational study. Setting ICU of a veterinary teaching hospital. Animals One hundred and five client‐owned dogs. Measurements and Main Results Jugular venous blood samples were collected from each patient on admission to determine: total plasma protein (TP), albumin (Alb), blood urea nitrogen (BUN), glucose (Glu), hematocrit (HCT), Na+, Cl−, K+, phosphate (Pi), pH, PvCO2, bicarbonate (HCO3−), anion gap (AG), adjusted anion gap for albumin (AGalb) or phosphate (AGalb‐phos), standardized base excess (SBE), strong ion difference (SID), concentration of nonvolatile weak buffers (Atot), and strong ion gap (SIG). Patients were divided in 2 groups according to the severity of the hypoalbuminemia: mild (Alb = 21–25 g/L) and severe (Alb ≤20 g/L). All parameters were compared among groups. Patients with severe hypoalbuminemia showed significant decrease in TP (P = 0.011), Atot (P = 0.050), and a significant increase in adjusted AG (P = 0.048) and the magnitude of SIG (P = 0.011) compared to animals with mild hypoalbuminemia. According to the HH approach, the most frequent imbalances were simple disorders (51.4%), primarily metabolic acidosis (84.7%) associated with a high AG acidosis. However, when using the quantitative method, 58.1% of patients had complex disorders, with SIG acidosis (74.3%) and Atot alkalosis (33.3%) as the most frequent acid–base imbalances. Agreement between methods only matched in 32 cases (kappa < 0.20). Conclusions The agreement between the HH and quantitative methods for interpretation of acid–base balance was poor and many imbalances detected using the quantitative approach were missed using the HH approach. Further studies are necessary to confirm the clinical utility of using the quantitative approach in the decision‐making process of the severely ill hypoalbuminemic patients.